A method for preparing high-strength porcelain insulator slurry

Through the pretreatment and mixing process for different raw materials, the problem of unreasonable particle grading in the preparation of traditional porcelain insulator slurry is solved, and porcelain insulator products with high strength and high electrical performance is achieved, reducing the quality problems during the drying process.

CN119786171APending Publication Date: 2025-04-08SINOMA JIANGXI ELECTRICAL PORCELAIN ELECTRIC CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510014898.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In the traditional porcelain insulator slurry preparation method, it is difficult to grind the raw materials evenly during the ball milling process, resulting in unreasonable particle grading, affecting product strength and drying performance, and prone to quality problems such as cracking and umbrella loss.

Method used

Different pretreatment equipment and processes are used to grind raw materials with water. Raw materials such as alumina, alumina, feldspar and hard clay are ground through sand mills and ball mills. The soft clay is slurried through slurryers to ensure that the particle size of each raw material meets the requirements. Then, mix evenly through the slurry mixer to adjust the composition distribution ratio and moisture content of the slurry.

Benefits of technology

It effectively improves the particle grading and assembly ratio of the slurry, improves the strength and electrical performance of the porcelain insulator, reduces quality problems such as cracking and umbrella loss during the drying process, and improves the drying pass rate and strength of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786171A_ABST
    Figure CN119786171A_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a high-strength porcelain insulator slurry, wherein the raw materials of the porcelain insulator slurry include alumina, alumina, feldspar, hard clay and soft clay; firstly, different pretreatment equipment is used to grind with water to obtain various slurries according to the different grinding properties of the above raw materials, and then the various slurries are mixed by a slurry mixer, so that the particle gradation of the final slurry reaches the expected; the slurry preparation process of the present invention is to treat each raw material with different grinding properties, combined with the expected particle size requirements of the raw material, and adopt different processing technologies for separate treatment. Then the various slurries are mixed by a slurry mixer, so that the particle gradation and component ratio of the final slurry are optimized, thereby improving the process performance of the mud material, reducing process defects such as drying and cracking, and improving the drying qualified rate and product strength of the product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0002] The invention relates to the technical field of porcelain insulator preparation technology, in particular to a method for preparing high-strength porcelain insulator slurry. Background Art

[0003] At present, the preparation process of porcelain insulator industry is as follows: batching → ball milling → sieving and iron removal → mud squeezing → rough mud smelting → aging → fine mud smelting → molding → drying → glazing → firing → assembly → testing → packaging and delivery. The purpose of batching and ball milling is to weigh various raw materials (such as bauxite or alumina powder, feldspar, various clays) and water according to a certain ratio and add them to the ball mill. The grinding media in the ball mill are alumina balls, pebbles, etc. The ball mill rotates and drives the balls and pebbles to rotate together under the action of centrifugal force. They rise to a certain height and fall like parabolic objects under the action of gravity, crushing the materials. At the same time, the mutual sliding between the grinding media during the rotation process will also grind the materials themselves, so that various raw materials can be fully ground and mixed in water to form slurry for insulator preparation.

[0004] The disadvantage of the above-mentioned traditional slurry preparation method is that various raw materials are added at one time and ground together. Within the same ball milling time, some difficult-to-grind materials (such as bauxite, alumina powder, feldspar and hard clay) are not fully ground, while some easier-to-grind materials (such as various soft clays) are ground too finely and cannot effectively form a more reasonable particle grading. If the ball milling time is reduced, the particles of lean raw materials (such as bauxite, alumina powder, feldspar and hard clay) are coarser, affecting the strength of the product; if the ball milling time is increased, the particles of plastic raw materials (such as various soft clays) are too fine, affecting the drying performance, and are prone to problems such as drying umbrellas and cracking, affecting the qualified rate of the product. Summary of the invention

[0005] The present invention aims to at least partially overcome the above technical problems and / or other potential problems existing in the prior art: provide a method for preparing a high-strength porcelain insulator slurry, mainly for preparing a slurry of a porcelain insulator whose raw materials include alumina, alumina powder, feldspar, hard clay and soft clay. The preparation method of the present invention can effectively ensure that the porcelain insulator blank is not prone to quality problems such as cracking and falling off during the drying process, and has high strength after firing, which greatly improves the electrical performance and mechanical properties of the porcelain insulator.

[0006] The first object of the present invention is to provide a method for preparing high-strength porcelain insulator slurry, wherein the raw materials of the porcelain insulator slurry include alumina, alumina, feldspar, hard clay and soft clay; firstly, different pretreatment equipment is used to perform water-adding grinding treatment according to the different grinding properties of the above raw materials to obtain various slurries, and then the various slurries are mixed by a slurry mixer, so that the particle gradation of the final slurry reaches the expected level.

[0007] As an optimization, the alumina and alumina powder in the raw materials are ground separately by sand mill, the feed fineness is controlled at 250-325 mesh, the slurry moisture is 50-70%, and the output particle size is controlled by adjusting the grinding time according to different needs.

[0008] As an optimization, the feldspar and hard clay in the raw materials are ground by ball mills respectively, and the fineness of the feldspar input is controlled to be 100-200 mesh, the fineness of the hard clay input is 40-100 mesh, the slurry moisture is 40-60%, and the output particle size is controlled by adjusting the grinding time according to different needs.

[0009] As an optimization, the soft clay in the raw material is pulped by a pulping machine, and the volume of the soft clay input is controlled to be 100cm 3 Below, the slurry moisture content is 50-70%.

[0010] Preferably, the hard clay is one or more of low plasticity clays having a plasticity index of 1-7.

[0011] Preferably, the hard clay is one or more of Zhangcun clay and Jingyang clay.

[0012] Preferably, the soft clay is one or more of high plasticity clays with a plasticity index greater than 15.

[0013] Preferably, the soft clay is one or more of Jilin ball clay, Faku clay and Zuoyun clay.

[0014] A second object of the present invention is to provide a method for preparing a high-strength porcelain insulator, comprising the following steps: 1) Grind alumina and aluminum oxide with sand mills, control the feed fineness to 250-325 mesh, slurry moisture to 50-70%, and control the output particle size of alumina and aluminum oxide to 500-600 mesh; Grind feldspar and hard clay with ball mills, control the feed fineness of feldspar to 100-200 mesh, the feed fineness of hard clay to 40-100 mesh, slurry moisture to 40-60%, the output particle size of feldspar to 250-325 mesh, and the output particle size of hard clay to 250-325 mesh; Use pulping machine to pulp soft clay, control the feed volume of soft clay to 100cm 3 Below, the slurry moisture is 50-70%; 2) The alumina slurry, alumina slurry, feldspar slurry, hard clay slurry and soft clay slurry prepared in step 1) are mixed uniformly by a slurry mixer; the water content of the mixed slurry is controlled to be 55-65%, and the weight proportion of each solid raw material is as follows: 20-30 parts of alumina, 10-20 parts of alumina, 10-15 parts of feldspar, 10-20 parts of hard clay and 35-45 parts of soft clay; 3) The mixed slurry prepared in step 2) is sieved to remove iron impurities, and then filtered to remove water to form a mud cake, and then subjected to rough mud smelting, aging, fine mud smelting, molding, drying, glazing, and firing to prepare a high-strength porcelain insulator.

[0015] The beneficial effects of the present invention are as follows: the slurry preparation process of the present invention is based on the different grinding properties of each raw material, combined with the desired particle size requirements of the raw material, and different processing technologies are used for separate processing. Then the various slurries are mixed through a slurry mixer, so that the particle grading and component ratio of the final slurry are optimized, thereby improving the mud material process performance, reducing process defects such as drying and cracking, and improving the drying qualification rate and product strength of the product. The preparation method of the present invention can effectively ensure that the porcelain insulator blank is not prone to quality problems such as cracking and falling off during the drying process, and has high strength after firing, which greatly improves the electrical properties and mechanical properties of the porcelain insulator. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a schematic diagram of the graded grinding process of the porcelain insulator slurry raw materials in Example 1. DETAILED DESCRIPTION

[0017] The present invention is further described in detail below with specific examples, but the present invention is not limited to the following specific examples.

[0018] Example 1 1) Grind alumina and alumina separately with a sand mill, control the feed fineness of alumina and alumina to 250-325 mesh, the moisture of alumina slurry to 65%, the moisture of alumina slurry to 60%, and the particle size of alumina and alumina output to 500-600 mesh; Grind feldspar and Zhangcun soil separately with a ball mill, control the feed fineness of feldspar to 100-200 mesh, the feed fineness of Zhangcun soil to 40-100 mesh, the moisture of feldspar slurry to 45%, the moisture of Zhangcun soil slurry to 50%, and the particle size of feldspar and Zhangcun soil output to 250-325 mesh; Grind Jilin ball soil and Zuoyun soil separately with a pulping machine, control the feed volume of Jilin ball soil and Zuoyun soil to 100cm 3 Below, the moisture content of Jilin ball soil slurry is 65%, and the moisture content of Zuoyun soil slurry is 60%; 2) The alumina slurry, alumina slurry, feldspar slurry, Zhangcun soil slurry, Jilin ball soil slurry and Zuoyun soil slurry prepared in step 1) are mixed evenly using a slurry mixer; the mixed slurry has a moisture content of 60%, and the proportions of each solid raw material are as follows: 25kg alumina, 15kg alumina, 10kg feldspar, 15kg Zhangcun soil, 25kg Jilin ball soil, and 10kg Zuoyun soil; 3) The mixed slurry prepared in step 2) is sieved to remove iron impurities, and then filtered to remove water to form a mud cake, and then subjected to coarse mud smelting, aging, and refined mud smelting, forming into strips, drying, and finally sintering at 1260° C. to prepare insulator test strip 1#.

[0019] Example 2 The difference between this embodiment and embodiment 1 is that the proportion of each solid raw material in step 2) is as follows: 25 kg of bauxite, 15 kg of alumina, 10 kg of feldspar, 15 kg of Zhangcun soil, 25 kg of Jilin ball clay, and 10 kg of Zuoyun soil; the other process conditions are the same as those in embodiment 1, and an insulator test strip 2# is prepared.

[0020] Example 3 The difference between this embodiment and embodiment 1 is that the proportion of each solid raw material in step 2) is as follows: 20 kg of bauxite, 20 kg of alumina, 10 kg of feldspar, 15 kg of Zhangcun soil, 25 kg of Jilin ball clay, and 10 kg of Zuoyun soil; the other process conditions are the same as those in embodiment 1, and an insulator test strip 3# is prepared.

[0021] Example 4 The difference between this embodiment and embodiment 1 is that the proportion of each solid raw material in step 2) is as follows: 25 kg of bauxite, 15 kg of alumina, 10 kg of feldspar, 15 kg of Zhangcun soil, 10 kg of Jilin ball clay, and 25 kg of Zuoyun soil; the other process conditions are the same as those in embodiment 1, and an insulator test bar 4# is prepared.

[0022] Example 5 The difference between this embodiment and embodiment 1 is that the proportion of each solid raw material in step 2) is as follows: 20 kg of bauxite, 15 kg of alumina, 10 kg of feldspar, 15 kg of Zhangcun soil, 25 kg of Jilin ball clay, and 15 kg of Zuoyun soil; the other process conditions are the same as those in embodiment 1, and an insulator test bar 5# is prepared.

[0023] Example 6 The difference between this embodiment and embodiment 1 is that the proportion of each solid raw material in step 2) is as follows: 30 kg of bauxite, 10 kg of alumina, 10 kg of feldspar, 15 kg of Zhangcun soil, 25 kg of Jilin ball clay, and 10 kg of Zuoyun soil; the other process conditions are the same as those in embodiment 1, and an insulator test bar 6# is prepared.

[0024] Example 7 The difference between this embodiment and embodiment 1 is that the proportion of each solid raw material in step 2) is as follows: 30 kg of bauxite, 10 kg of alumina, 10 kg of feldspar, 15 kg of Zhangcun soil, 25 kg of Jilin ball clay, and 10 kg of Zuoyun soil; the other process conditions are the same as those in embodiment 1, and an insulator test bar 7# is prepared.

[0025] Comparative Example 1 1) Weigh the following raw materials: 25kg bauxite, 15kg alumina, 10kg feldspar, 15kg Zhangcun soil, 25kg Jilin ball soil, 10kg Zuoyun soil; 2) The raw materials in step 1) were mixed, 60 wt % of water was added, and the mixture was ground in a ball mill for 8 h to obtain a mixed slurry; 3) The mixed slurry prepared in step 2) is sieved to remove iron impurities, and then filtered to remove water to form a mud cake, and then subjected to coarse mud smelting, aging, and refined mud smelting, forming into strips, drying, and finally sintering at 1260° C. to prepare comparative test strip 1#.

[0026] Comparative Example 2 The difference between this comparative example and comparative example 1 is that the raw material ratios in step 1) are as follows: 25 kg of bauxite, 15 kg of alumina, 10 kg of feldspar, 15 kg of Zhangcun soil, 25 kg of Jilin ball clay, and 10 kg of Zuoyun soil; the other process conditions are the same as those in comparative example 1, and comparative test strip 2# is prepared.

[0027] Comparative Example 3 The difference between this comparative example and comparative example 1 is that the raw material ratios in step 1) are as follows: 20 kg of bauxite, 20 kg of alumina, 10 kg of feldspar, 15 kg of Zhangcun soil, 25 kg of Jilin ball clay, and 10 kg of Zuoyun soil; the remaining process conditions are the same as those in comparative example 1, and comparative test strip 3# is prepared.

[0028] Comparative Example 4 The difference between this comparative example and comparative example 1 is that the raw material ratios in step 1) are as follows: 25 kg of bauxite, 15 kg of alumina, 10 kg of feldspar, 15 kg of Zhangcun soil, 10 kg of Jilin ball clay, and 25 kg of Zuoyun soil; the remaining process conditions are the same as those in comparative example 1, and comparative test bar 4# is prepared.

[0029] Comparative Example 5 The difference between this comparative example and comparative example 1 is that the raw material ratios in step 1) are as follows: 20 kg of bauxite, 15 kg of alumina, 10 kg of feldspar, 15 kg of Zhangcun soil, 25 kg of Jilin ball clay, and 15 kg of Zuoyun soil; the other process conditions are the same as those in comparative example 1, and comparative test bar 5# is prepared.

[0030] Comparative Example 6 The difference between this comparative example and comparative example 1 is that the raw material ratios in step 1) are as follows: 30 kg of bauxite, 10 kg of alumina, 10 kg of feldspar, 15 kg of Zhangcun soil, 25 kg of Jilin ball clay, and 10 kg of Zuoyun soil; the other process conditions are the same as those in comparative example 1, and comparative test bar 6# is prepared.

[0031] Comparative Example 7 The difference between this comparative example and comparative example 1 is that the raw material ratios in step 1) are as follows: 30 kg of bauxite, 10 kg of alumina, 10 kg of feldspar, 15 kg of Zhangcun soil, 25 kg of Jilin ball clay, and 10 kg of Zuoyun soil; the other process conditions are the same as those in comparative example 1, and comparative test bar 7# is prepared.

[0032] Performance Testing The qualified drying rate of the blanks of Examples 1-7 was tested to be 90%, while the qualified drying rate of the blanks of Comparative Examples 1-7 was about 80%, and the qualified drying rate was increased by about 10%. The porcelain test strips of Examples 1-7 and Comparative Examples 1-7 were tested for flexural strength, and the test results are shown in the following table: Comparison test strips 1# 2# 3# 4# 5# 6# 7# average value Strength (Mpa) 164.37 166.20 168.89 167.06 171.17 165.25 177.09 168.58 Insulator test strips 1# 2# 3# 4# 5# 6# 7# average value Strength (Mpa) 183.35 191.36 186.96 177.87 191.94 192.73 186.52 187.25 It can be seen from the above table that the strength of the test bars of Examples 1-7 is increased by about 10 MPa relative to that of Comparative Examples 1-7.

[0033] The above are only examples of the features of the present invention and do not constitute any limitation on the protection scope of the present invention. Any technical solution formed by equivalent exchange or equivalent replacement falls within the protection scope of the present invention.

Claims

1. A method for preparing a high-strength porcelain insulator slurry, characterized in that: The raw materials of the porcelain insulator slurry include alumina, alumina, feldspar, hard clay and soft clay. First, according to the different grinding properties of the above raw materials, different pretreatment equipment is used to add water and grind to obtain various slurries, and then the various slurries are mixed by a slurry mixer, so that the particle gradation of the final slurry reaches the expected.

2. The method for preparing the high-strength porcelain insulator slurry according to claim 1, characterized in that: The alumina and alumina powder in the raw materials are ground separately by sand mill, the feed fineness is controlled at 250-325 mesh, the slurry moisture is 50-70%, and the output particle size is controlled by adjusting the grinding time according to different needs.

3. The method for preparing the high-strength porcelain insulator slurry according to claim 2, characterized in that: The feldspar and hard clay in the raw materials are ground separately by ball mills, and the fineness of the feldspar input is controlled to be 100-200 mesh, the fineness of the hard clay input is 40-100 mesh, the slurry moisture is 40-60%, and the output particle size is controlled by adjusting the grinding time according to different needs.

4. The method for preparing the high-strength porcelain insulator slurry according to claim 3, characterized in that: The soft clay in the raw material is pulped with a pulping machine, and the volume of the soft clay input is controlled to be 100cm 3 Below, the slurry moisture content is 50-70%.

5. The method for preparing the high-strength porcelain insulator slurry according to claim 4, characterized in that: The hard clay is one or more of low plasticity clays with a plasticity index of 1-7.

6. The method for preparing the high-strength porcelain insulator slurry according to claim 5, characterized in that: The hard clay is one or more of Zhangcun clay and Jingyang clay.

7. The method for preparing high-strength porcelain insulator slurry according to claim 6, characterized in that: The soft clay is one or more of high plasticity clays with a plasticity index greater than 15.

8. The method for preparing the high-strength porcelain insulator slurry according to claim 7, characterized in that: The soft clay is one or more of Jilin ball clay, Faku clay and Zuoyun clay.

9. A method for preparing a high-strength porcelain insulator using any one of claims 1 to 8, comprising the following steps: 1) Grind alumina and aluminum oxide with sand mills, control the feed fineness to 250-325 mesh, slurry moisture to 50-70%, and control the output particle size of alumina and aluminum oxide to 500-600 mesh; Grind feldspar and hard clay with ball mills, control the feed fineness of feldspar to 100-200 mesh, the feed fineness of hard clay to 40-100 mesh, slurry moisture to 40-60%, the output particle size of feldspar to 250-325 mesh, and the output particle size of hard clay to 250-325 mesh; Use pulping machine to pulp soft clay, control the feed volume of soft clay to 100cm 3 Below, the slurry moisture is 50-70%; 2) The alumina slurry, alumina slurry, feldspar slurry, hard clay slurry and soft clay slurry prepared in step 1) are mixed uniformly by a slurry mixer; the water content of the mixed slurry is controlled to be 55-65%, and the weight proportion of each solid raw material is as follows: 20-30 parts of alumina, 10-20 parts of alumina, 10-15 parts of feldspar, 10-20 parts of hard clay and 35-45 parts of soft clay; 3) The mixed slurry prepared in step 2) is sieved to remove iron impurities, and then filtered to remove water to form a mud cake, and then subjected to rough mud smelting, aging, fine mud smelting, molding, drying, glazing, and firing to prepare a high-strength porcelain insulator.